The gamma-hemolysin locus of Staphylococcus aureus comprises three linked genes, two of which are identical to the genes for the F and S components of leukocidin - FOSTER, TIMOTHY (My University, 1993)
The Staphylococcus aureus gamma-hemolysin comprises two polypeptides, whereas the gamma-hemolysin locus (hlg) contains three open reading frames. The hlgA and hlgB genes encode the gamma 1 and gamma 2 components, respectively. The HlgB protein (gamma 2) has 27% residue identity with S. aureus alpha-toxin. Surprisingly, hlgB and hlgC are 98.5 and 99.1% identical to the lukF and lukS genes, respectively, encoding the F and S components of the Panton-Valentine leukocidin.